The NFATc1/P2X7 receptor relationship in human intervertebral disc cells - Notarangelo, Maria Pina; Penolazzi, Letizia; Lambertini, Elisabetta; Falzoni, Simonetta; De Bonis, Pasquale; Capanni, Cristina; Di Virgilio, Francesco; Piva, Roberta (Frontiers in Cell and Developmental Biology, 2024)
A comprehensive understanding of the molecules that play key roles in the physiological and pathological homeostasis of the human intervertebral disc (IVD) remains challenging, as does the development of new therapeutic treatments. We recently found a positive correlation between IVD degeneration and P2X7 receptor (P2X7R) expression increase both in the cytoplasm and in the nucleus. By immunocytochemistry, RT-PCR, overexpression, and chromatin immunoprecipitation we found that NFATc1 and hypoxia-inducible factor-1α (HIF-1α) are critical regulators of P2X7R. Both transcription factors are recruited at the promoter of P2RX7 gene and involved in its positive and negative regulation, respectively. Furthermore, by proximity ligation assay we revealed that P2X7R and NFATc1 form a molecular complex, and that P2X7R is closely associated with the lamin A/C, a major component of the nuclear lamina. Collectively, our study identifies for the first time P2X7R and NFATc1 as markers of IVD degeneration and demonstrates that both NFATc1 and lamin A/C are interaction partners of P2X7R.